A new interface element connecting 3D finite elements with non-coincident nodes to simulate delamination in composite laminates. (15th November 2020) - Trellu, A.; Bouvet, C.; Rivallant, S.; Ratsifandrihana, L.
Abstract: Composite failure phenomena remain complex and lead to over-size structures in many industries, involving long and costly experimental campaigns. Numerical approaches are a good alternative to decrease sizing costs. The Discrete Ply Model developed in Institut Clément Ader over these last ten years shows good results in simulation of impact and compression after impact of composite laminates, ply drop-offs, open hole tensile tests… But the present approach leads to certain limitations for complex stacking sequences and induces unwanted characteristic lengths between consecutive plies. A user element for delamination calculation is developed that allows to define an interface corresponding to the overlapping zone between the two volume elements of upper and lower plies, whereas this overlapping zone is not directly defined by nodes of the mesh (volume elements have non-coincident nodes). The present paper details the new interface element implementation, its validation from DCB and ENF test simulations, and then its improvement is discussed.